Estimasi Sumberdaya Endapan Nikel Laterit Menggunakan Metode IDW Pada Pit Rama PT. Tonia Mitra Sejahtera Kabupaten Bombana, Provinsi Sulawesi Tenggara - Muhammad Yasser Arsy Akbar; Erwin Anshari; Muhammad Ilham Kadar (OPHIOLITE: Jurnal Geologi Terapan, 2025)
PT. Tonia Mitra Sejahtera is a company engaged in the nickel laterite commodity mining industry with a production operation mining business permit area of approximately ± 5,891 Ha. Currently, the company plans to open a new mining block at Pit Rama with an area of ± 5 Ha. This study aims to determine the amount of resources contained in Pit Rama. This research method is a quantitative study that combines theory with data obtained in the field. The estimation method used is the Inverse Distance Weighted (IDW) method which is determined based on geological conditions and the results of basic statistical analysis that have been carried out with an average drill spacing of 25 meters. The results of the study obtained a total resource volume at Pit Rama of 655,352.56 m3 and has a tonnage of 991,796.88 tons with an average nickel content of 1.74%.